Impact of Epilepsy Surgery on Motor Performance - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The impact of epilepsy surgery on motor performance of 37 children (ages 1 month to 15 years) with refractory seizures was evaluated at the Wilhelmina University Children's Hospital, Utrecht, The Netherlands.